Optimization of MSW Feed for Waste to Energy Practices - T. Gebreegziabher; A.O. Oyedun; K.-L. Lam; H.K.M. Lee; C.-W. Hui (Chemical Engineering Transactions, 2012)
The rapid growth rate in the world population along with economical development is creating an environmental burden through energy consumption and solid waste generation. As a result of bulk solid waste generation, many countries are confronted with disposal problems. Countries are drafting policy frame works for reducing, reusing, recycling and treating waste, and to use the landfills as a final repository. But with treatment process inefficiencies and the proven negative environmental impacts of landfills, developing further landfills for treated waste disposal can't remain as the only option. Alternative ways for solid waste management need to be identified. Energy recovery from solid waste known as waste-to-energy (WTE) is one such alternative. Waste to Energy technologies such as modern incineration and gasification processes have been gaining popularity as they can significantly reduce the volume of solid wastes and at the same time produce a combination of heat and electricity. Any carbon rich solid waste can be burned to produce energy. But due to variability of properties, uneven combustion in the chamber can hamper the operation of incinerator. The unsteadiness of the combustion process can be adjusted by making appropriate solid waste blend that meet the specification of combustor feed. Due to variations of physical and chemical properties, appropriate blend feeds of incinerator previously are made by applying extensive trial and error methods accompanied with laboratory and pilot scale testing of simulated synthetic wastes for stable combustion. In this work typical industrial origin solid waste is considered and optimum feed stock blending amount with its gross calorific value was predicted and was cross checked with the specific values given in literature.